Sustainable Asian House : Thailand, Malaysia, Singapore, Indonesia, Philippines. - Paul (Tuttle Publishing, 2013)
Today's byword is sustainability, and in few arenas is that more evident than in architecture. The Sustainable Asian House celebrates the new architectural vocabulary of environmental, social, and cultural sustainability as it is now emerging in Southeast Asia, specifically Thailand, Malaysia, Singapore, Indonesia, and the Philippines. The houses in this book are an exciting representation of the region's reinterpretation of tropical architecture and its growing interest in traditional materials and craftsmanship. There is a new emphasis on fresh air, natural light, and spatial variety. Designe.